Valor nutritivo do feno de Cynodon - Vaquero aditivado com ureia e submetido a diferentes teores de umidade - Mazzochin, Eliana Aparecida dos Reis (2013)
The experiment was conducted to evaluate the bromatological composition, thein vitro digestibility, and the fractionation of Cynodon dactylon hay protein (Vaquero grass)treated with increasing doses of urea (0, 2.5 and 5%) based on the dry matter (DM), at different moisture contents (12, 18, 24 and 30%). The experiment was performed by a completely randomized design in a 4x3 factorial design with four replications. Urea was dissolved in sufficient water quantity to raise the moisture content of the hay to the desired values. The material was stored in plastic bags (11.39 kg/bag), which were sealed for 30 days. Afterwards, they were opened and samples were collected for laboratory analysis. It was found that the DM contente decreased with increasing doses of urea and moisture content. The total nitrogen (TN) increased with increasing doses of urea, and it was reduced to make the moisture content higher. The amounts of neutral detergent insoluble nitrogen (NDIN) and acid detergent insoluble nitrogen (ADIN) increased according to the moisture content and decreased as the dose of urea applied increased. NDIN values in relation to total nitrogen (NDIN/TN) decreased with increasing dose of urea, and the largest decreases were observed in treatments with lower moisture. The contents of ADIN in relation to the total nitrogen (ADIN/TN) were reduced with higher doses of urea, and higher levels of reduction occurred in 30% moisture. The ammoniated hay with different moisture contents increased levels of A fraction in relation to the total nitrogen, but did not affect B1. However, The B3 and C fractions decreased in response to ammoniation. The increase in the dose of urea promoted a reduction in the levels of neutral detergent fiber and acid detergent fiber. The contents of hemicellulose and cellulose decreased with increasing doses of urea, these reductions being more pronounced with increasing moisture content. There was no effect (P > 0.05) of urea doses, moisture content and interaction of the variables in the amount of lignin. The in vitro dry matter digestibility (IVDMD) was influenced by the dose of urea (P <0.05) and the moisture content (P<0.05). The higher IVDMD value was obtained for the level of 5% urea and 30% moisture. The in vitro digestibility of organic matter was not affected (p> 0.05) for any variable. The urea application with 12, 18, 24 or 30% moisture was favorable for increasing the nutritional value of the Vaquero grass